1972
DOI: 10.1073/pnas.69.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus: Transformation, Cytopathic Changes, and Viral Antigens in Squirrel Monkey and Marmoset Leukocytes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
207
1

Year Published

1975
1975
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(211 citation statements)
references
References 18 publications
3
207
1
Order By: Relevance
“…We have synthesized several, non-chemically modi®ed antisense oligodeoxynucleotides directed to di erent potential target sequences within the translation initiation region of EBV LMP1 mRNA. The e ects of the incubation of LMP1 antisense oligodeoxynucleotides were studied on B95.8 cells, EBV transformed marmoset leukocytes (Miller et al, 1972). We have found that one oligomer, denominated AS2, encompassing the predicted translation initiation site of LMP1 mRNA expressed in B95.8 cells (see Table 1), inhibits cell proliferation, leads to a substantial loss of LMP1 mRNA and signi®cantly decreases the intracellular concentration of LMP1 protein as reported below.…”
mentioning
confidence: 69%
“…We have synthesized several, non-chemically modi®ed antisense oligodeoxynucleotides directed to di erent potential target sequences within the translation initiation region of EBV LMP1 mRNA. The e ects of the incubation of LMP1 antisense oligodeoxynucleotides were studied on B95.8 cells, EBV transformed marmoset leukocytes (Miller et al, 1972). We have found that one oligomer, denominated AS2, encompassing the predicted translation initiation site of LMP1 mRNA expressed in B95.8 cells (see Table 1), inhibits cell proliferation, leads to a substantial loss of LMP1 mRNA and signi®cantly decreases the intracellular concentration of LMP1 protein as reported below.…”
mentioning
confidence: 69%
“…The consistent failure to induce tumors with this preparation (Werner et al, 19726;Falk et al, 1974) corresponds to the lack of transforming activity after infection of umbilical cord lymphocytes (Klein et al, 1972;Miller et al, 1972). The marmoset system appears to offer an approach to test strain differences of various EBV isolates.…”
Section: Discussionmentioning
confidence: 90%
“…Shope and co-workers induced malignant lymphomas in four of eight cotton-top marmosets by inoculation of cell-free virus extracted from a marmoset lymphoblastoid line 895-8 originally transformed in vitro (Miller et al, 1972) by EBV isolated from an IM cell line. These results were confirmed by Falk and his colleagues, also using B95-%derived virus in cotton-top marmosets.…”
Section: Of Ebv Directly Derived Fvom Cells Of Im Originmentioning
confidence: 99%
“…SCC12F cells were seeded at 10 5 cells per 10 cm Petri dish (Corning, Gri ths and Nielsen Ltd, Billingshurst, UK). B95-8, an EBV genome-positive marmoset cell line (Miller et al, 1972), was cultured in RPMI 1640 medium containing 10% heat-inactivated FCS. Cultures were incubated at 378C in a fully humidi®ed, 5% CO 2 atmosphere, and medium was changed twice weekly.…”
Section: Cell Culturementioning
confidence: 99%